2014
DOI: 10.1088/0957-4484/25/30/305601
|View full text |Cite
|
Sign up to set email alerts
|

Fe doped TiO2–graphene nanostructures: synthesis, DFT modeling and photocatalysis

Abstract: In this work, Fe-doped TiO(2) nanoparticles ranging from a 0.2 to 1 weight % were grown from the surface of graphene sheet templates containing -COOH functionalities using sol-gel chemistry in a green solvent, a mixture of water/ethanol. The assemblies were characterized by a variety of analytical techniques, with the coordination mechanism examined theoretically using the density functional theory (DFT). Scanning electron microscopy and transmission electron microscopy images showed excellent decoration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
1
17
1
Order By: Relevance
“…Contrary to our findings, removal efficiencies for 10 mg L −1 HA were reported to increase when Fe 3+ ions were doped into the TiO 2 nanotubes and subjected to O 3 prior to degradation [21]. On the other hand, Baek et al [20] reported low photocatalytic activity for the removal of HA using Fe-TiO 2 /SAC under UVC light (100-280 nm). Changing Fe contents (0.4-0.8 wt%) and the light source to UVA (315-400 nm) resulted in higher photocatalytic activity.…”
Section: Kinetic Considerationscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, removal efficiencies for 10 mg L −1 HA were reported to increase when Fe 3+ ions were doped into the TiO 2 nanotubes and subjected to O 3 prior to degradation [21]. On the other hand, Baek et al [20] reported low photocatalytic activity for the removal of HA using Fe-TiO 2 /SAC under UVC light (100-280 nm). Changing Fe contents (0.4-0.8 wt%) and the light source to UVA (315-400 nm) resulted in higher photocatalytic activity.…”
Section: Kinetic Considerationscontrasting
confidence: 99%
“…Moreover, aromatic compounds as phenol and chlorinated phenol derivatives, 4-nitrophenol, benzene, and nitrobenzene, aliphatic compounds as dichloromethane, 1,2-dichloroethane, formic acid and acetic acid were also used as substrates. More specifically, 17␤-estradiol was investigated under visible light using a solar simulator [20]. However, all of these model compounds are in the molecular weight range of 46 g mol −1 to 272 g mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…As proposed above, •OH served as putative contributors to the removal of NO, where P25 and the as-prepared materials were used as catalysts to decompose H2O2. As shown in Figure 10, the observed hyperfine splitting constants for the 1:2:2:1 signal (aN = aH = 14.9 G) were the typical spectrum shape of the DMPO-OH spin adduct and were in good accordance with the values in the literature [44]. What is more, the concentration of •OH was in the order of: 2% Fe-TiO2 + H2O2 > TiO2 + H2O2 > P25 + H2O2 > H2O2.…”
Section: Structural Properties Of Catalystsupporting
confidence: 87%
“…The details of the process can be found in Wiedmer and Sánchez [44,56]. Specially, the operating conditions were set as follows: modulation frequency (100 kHz), modulation amplitude (4 G), resonance frequency (9.87 GHz), sweep width (200 G), microwave power (19.22 mW), centre field (3522 G).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The N and/or S-doped BiOBr products exhibit lower band gaps than that of pure BiOBr. It is well known that the indirect band gap semiconductor helps to obtain excellent photocatalytic activity because the excited electrons must be emitted to conduction band by traveling certain k-space distance, which reduces the recombination probability of the photogenerated electrons and holes [26][27][28]. The total density of states and partial density of states of the products have been illustrated according with the energy range of band structure, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%